LEMBAGA PENDIDIKAN ISLAM DI INDONESIA: KAJIAN DESKRIPSI-ANALITIK MODEL LEMBAGA PENDIDILAN ISLAM - Maunah, Binti (STAIN Kediri, 2015)
Islamic educational institutions, in general, play a significant role in the world of education. Through a learning process, these institutions should be able to bring students towards national education goals and become a mirror for other educational institutions. This article attempts to examine Islamic educational intuitions, both formal and informal, in Indonesia focusing on their models. The discussion centers on two largest models of Islamic educations institutions in Indonesia, which pesantren (non-formal) and madrasah (formal). It is true that diversification of Islamic educational institutions supported with clear objectives and focused on professionaldifferentiation is a good, effective, and efficient way of education. Nevertheless, this article argues that such diversification will only lead to duplications, uselessness and ineffectiveness if the term means only pseudodiversification with outer and artificial purposes.Keywords: Lembaga Pendidikan Islam, Pesantren, Madrasah